NUMERICAL SIMULATION OF FLOW ROUND FREE SPANNING SUBMARINE PIPELINE AT HIGH REYNOLDS NUMBER - HU Qin; WAN ChangCheng; XIAO Xiang; WANG Chuan (Jixie qiangdu)
Free spanning submarine pipeline work in the harsh condition and has many failure modes. Vortex-induced vibration is a significant cause leading to its fatigue failure. In order to study the law about different spanning clearance ratio and flow rate impacting on VIV strength of free spanning pipeline,this paper applied the software FLUENT to simulate twodimensional flow around actual diameter pipeline at high reynolds number and obtained the data about vortex shedding shape,lift coefficient and drag coefficient curves. The result indicates that: the lift coefficient amplitude and drag coefficient mean value of free spanning submarine pipeline decrease with clearance ratio increasing and gradually stabilize at last. In the case of small clearance ratio,lift extreme value is inequality on both sides of the pipe caused by the pipe bottom flow rate increasing. The lift coefficient amplitude and drag coefficient mean value present a trend of increasing first then decreasing with flow rate increaing,which is consistent with the conventional flow around a cylinder. Lift coefficient frequency increases with flow rate increaing and less affected by the clearance ratio. In engineering practice,water areas of high current velocity and large submarine spans should be avoid as much as possible to lay submarine pipelines and vortex-induced suppression device should be provided in danger sections.